Analisis Re-Layout Line Machining Oil Separator dengan Metode Value Stream Mapping dalam Meningkatkan Efisiensi Produktivitas di PT Astra Otoparts Divisi Nusametal - Rasyid, Adji Nur; Hendaryanto, Ignatius Aris; Setiawan, Widia; Winarno, Agustinus (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
The Oil Separator is a part produced by PT Astra Otoparts Nusametal Division. The products are manufactured on the machining line. The production process of part oil separator through several stages including CNC milling and lathe machining, washing part, and part verification process. Line machining oil separators have been found to have waste problems, namely moving manpower, waiting time process, and inappropriate processing, causing work imbalances in the production process. The job imbalance causes the daily production target not to be achieved as the company planned, so the customer needs cannot be met. The problem in this study was solved using the value stream mapping method to analyze the waste occurring and the impact resulting from the relayout line machining oil separator. The waste analysis is done by spreading questionnaires, waste weighting, value stream analysis tools selection (VALSAT), and cause analysis with fishbone diagrams. After that, some improvements were made to reduce the waste. Implementation of improvements resulted in a reduction in the number of work processes from 72 to 47. Thus, the lead time for process line machining oil separator decreased from 521 seconds/cycle to 444 seconds/ cycle with an increase in the total process cycle efficiency of 8.67%. In addition, the productivity of the previous average number of parts of 6575 pcs/day was increased to 7024 pcs / day and the manpower was reduced from five manpowers/day to three manpowers/day. Keywords: Process Cycle Efficiency, Re-layout, VALSAT, Value Stream Mapping